Induced seismicity at the UK 'hot dry rock' test site for geothermal energy production. Issue 1 (29th March 2018) - Li, Xun; Main, Ian; Jupe, Andrew
Summary: In enhanced geothermal systems (EGS), fluid is injected at high pressure in order to stimulate fracturing and/or fluid flow through otherwise relatively impermeable underlying hot rocks to generate power and/or heat. The stimulation induces microearthquakes whose precise triggering mechanism and relationship to new and pre-existing fracture networks are still the subject of some debate. Here, we analyse the data set for induced microearthquakes at the UK 'hot dry rock' experimental geothermal site (Rosemanowes, Cornwall). We quantify the evolution of several metrics used to characterise induced seismicity, including the seismic strain partition factor and the 'seismogenic index'. The results show a low strain partition factor of 0.01 per cent and a low seismogenic index indicating that aseismic processes dominate. We also analyse the spatio-temporal distribution of hypocentres, using simple models for the evolution of hydraulic diffusivity by (1) isotropic and (2) anisotropic pore-pressure relaxation. The principal axes of the diffusivity or permeability tensor inferred from the spatial distribution of earthquake foci are aligned parallel to the present-day stress field, although the maximum permeability is vertical, whereas the maximum principal stress is horizontal. Our results are consistent with a triggering mechanism that involves (1) seismic shear slip along optimally oriented pre-existing fractures, (2) a large component of aseismic slip with creep and (3) activation of tensile fractures as hydraulic conduits created by both the present-day stress field and by the induced shear slip, both exploiting pre-existing joint sets exposed in borehole data.